2005
DOI: 10.1186/1475-2875-4-45
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the methylene blue plus chloroquine combination in the treatment of uncomplicated falciparum malaria in young children of Burkina Faso [ISRCTN27290841]

Abstract: Background: Safe, effective and affordable drug combinations against falciparum malaria are urgently needed for the poor populations in malaria endemic countries. Methylene blue (MB) combined with chloroquine (CQ) has been considered as one promising new regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…This approach has recently been tested in clinical trials in the Nouna District of Burkina Faso (6,22). In this study, cases of MB toxicity or intolerance were not reported; however, a clear advantage over CQ monotherapy could not be observed either (24). Several reasons were proposed to be responsible for this clinical failure.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…This approach has recently been tested in clinical trials in the Nouna District of Burkina Faso (6,22). In this study, cases of MB toxicity or intolerance were not reported; however, a clear advantage over CQ monotherapy could not be observed either (24). Several reasons were proposed to be responsible for this clinical failure.…”
mentioning
confidence: 79%
“…A mechanism of reverting chloroquine resistance by MB as a glutathione reductase inhibitor has been proposed (10,15,32), and clinical trials assessing the safety and effectiveness of MB are already under way (6,24). In order to facilitate the design of future field studies and the interpretation of respective results, we have characterized the effects of the drug in cell cultures in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] In light of these results, it is not surprising that a clinical trial showed no advantage in using a combination of methylene blue and CQ over CQ monotherapy in an area with a high probability of chloroquine resistance. [56] …”
Section: Chloroquine Resistancementioning
confidence: 97%
“…[251] However, there is some degree of cross-resistance in the group of sulfonamides. The combination of dapsone and chlorproguanil (56) was evaluated in different clinical studies, [252][253][254] and was recently introduced as LapDap to the market. LapDap is active against strains carrying the triple mutant DHFR which are predominant in Africa, but it is inactive against strains harboring the quadruple mutant, abundant in Asia and South America.…”
Section: Chlorproguanil/dapsone (Lapdap)mentioning
confidence: 99%